Examining Research Patterns and Concepts in Relation to Frameworks for Sustainable Supply Chain Management (SSCM) - Ashish Patel; Anjana R (International Journal of Industrial and Product Design Engineering, 2024)
Structures abound in writing about Sustainable Supply Chain Management (SSCM). Nevertheless, no effort has been made to date to identify the anomalies in the systems that are in place now and the associated research trends. This research is motivated primarily by a survey of SSCM structures and feature abnormalities. The analysis also promotes new applications and aids in the analysis of SSCM structure constructions and exploration patterns. Using the Scopus database, it concludes a few systems in the SSCM domain for the period of 2005–2022, employing space specialists and an organised writing audit technique. It involves building squares and developments as well as employing a series of purposefully designed requirements-based questions to obtain patterns. In specifically, system arrange, utilisation stage catching current exploration patterns, and build organise are the three distinct stages at which it finds abnormalities. It also provides intricacies at the level of development and Structural Square. As such, it provides guidance for reducing anomalies and possible modifications to current frameworks. It revealed current developments and sub-builds and provided information about upcoming business changes that will impact the SSCM industry. It also teaches about the advantages and disadvantages of each system. The inquiry will push for new procedures to promote applications and reduce irregularities, which will aid in changes or updates to current structures. This unique report helps with system development by identifying anomalies at every step, provides a structure-based survey, and illustrates study tendencies. It aids in reducing anomalies and provides guidance for alterations to the SSCM structure while considering upcoming challenges.
Keywords: 3-D; NGO; SSCM Frame work; Sustainable Supply Chain Management (SSCM); XYZ Dimentional